The development of knowledge of content and teaching task instruments for pre-service mathematics teacher - Suprihatiningsih, Siti; Masriyah, Masriyah; Ekawati, Rooselyna (Intelektual Pustaka Media Utama, 2025)
The knowledge of the materials to be taught to the students is the basic knowledge that preservice mathematics teachers should possess, as they need to prepare themselves for teaching. In order to research preservice teachers’ understanding of the subject matter and teaching skils, valid and reliable test instruments are required. Knowledge of content and teaching (KCT) is one of the tools that can be used. This research was conducted using the Plomp model. Based on the research results, it was found that the KCT task instruments are valid, reliable, and legible. The instruments were utilized in this study with several revisions to describe the content and teaching knowledge of the subjects. The results of this investigation strongly support the use of KCT instruments. This tool is crucial to implement in understanding the capability of preservice mathematics educators in planning and successfully executing math lessons. Additionally, future research should be conducted on content understanding and classroom instruction on mathematics education. Such research will be able to reveal information on the expertise and experience of prospective mathematics teachers.